2019
DOI: 10.1111/joor.12912
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prosthetic status and dementia on the chewing efficiency of seniors in nursing homes

Abstract: Background:The oral health of seniors in nursing homes is compromised.Furthermore, reduced chewing efficiency is described to be associated with reduced cognition. However, studies investigating how prosthetic status affects the chewing efficiency of nursing home residents are not available.Objective: To evaluate associations between prosthetic status, dementia and chewing efficiency of seniors in nursing homes. Methods:This study was performed in nine nursing homes. In addition to assessing the general and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 35 publications
5
25
1
Order By: Relevance
“…Therefore, it can be hypothesised that, despite the tooth loss and absence of dentures, the volunteers may have used the remaining teeth to chew, 29 which may explain the intermediate masticatory performance. By comparing the results of this study with a previous investigation, we observed that our participants had a better masticatory performance (lower VOH) than the participants of a German report 5 (VOH mean ± SD=0.590 ± 0.250).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, it can be hypothesised that, despite the tooth loss and absence of dentures, the volunteers may have used the remaining teeth to chew, 29 which may explain the intermediate masticatory performance. By comparing the results of this study with a previous investigation, we observed that our participants had a better masticatory performance (lower VOH) than the participants of a German report 5 (VOH mean ± SD=0.590 ± 0.250).…”
Section: Discussionsupporting
confidence: 57%
“…3,4 Tooth loss, when not replaced by dentures, compromises mastication. 5,6 Considering that chewing and swallowing are the first stages of food digestion, 7 edentulism 8 and the absence of prosthetic rehabilitation 9 may affect food and nutrient intake. Consequently, the nutritional status of the elders could be affected by such factors.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Scores could therefore range from 0 to 30 points. As recommended in several previous studies, participants attaining scores of fewer than 24 classified as having cognitive impairment. [25][26][27][28] All examinations were performed by two dentists who had been trained at the Memory Clinic of the University of Heidelberg before the start of the study.…”
Section: Sociodemographic Variables and Cognitive Impairmentmentioning
confidence: 99%
“…Furthermore, it has been determined that the type of prosthetic restoration also has an effect on chewing efficiency of adults and seniors. 23,24 However, only limited information is available regarding the chewing efficiency of nursing-home residents. Furthermore, to the best of the authors' knowledge, no study has investigated the effect of chewing efficiency on the OHRQoL of nursing-home residents.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of health teeth and functional dentures, as they are related to adequate nutrient consumption, may favor a good general health and quality of life of the elderly [5,6]. However, it is suggested that the absence of functional occluding tooth pairs worsens the chewing ability, which may lead to modifications in eating habits, food and nutritional intake, causing malnutrition [7,8]. In this context, considering the high prevalence of tooth loss, the reduced number of functional occluding tooth pairs, the low use of dental dentures and the poor condition of removable dentures among institutionalized elderly, these individuals would have compromised chewing capacity, which may affect their nutritional status [7,8].…”
mentioning
confidence: 99%